Generalised anxiety and panic symptoms in the German National Cohort (NAKO) - Erhardt-Lehmann, Angelika; Gelbrich, Götz; Klinger-König, Johanna; Streit, Fabian; Kleineidam, Luca; Riedel-Heller, Steffi G.; Schmidt, Börge; Schmiedek, Florian; Wagner, Michael; Grabe, Hans J.; Rietschel, Marcella; Berger, Klaus; et al. (The world journal of biological psychiatry, 2023)
Anxiety disorders (AD) are common in the general population, leading to high emotional distress and disability. The German National Cohort (NAKO) is a population-based mega-cohort study, examining participants in 16 German regions. The present study includes data of the first 101,667 participants and investigates the frequency and severity of generalised anxiety symptoms and panic attacks (PA). The Generalised Anxiety Disorder Symptoms Scale (GAD-7) and the first part of the Patient Health Questionnaire Panic Disorder (PHQ-PD) were filled out by NAKO participants (93,002). We examined the correlation of GAD-7 and PHQ-PD with demographic variables, stress (PHQ-Stress), depression (PHQ-9) and childhood trauma (CTS). The total proportion of prior lifetime diagnoses of AD in the NAKO cohort reached 7.8%. Panic attacks were reported by 6.0% and possible/probable current GAD symptoms in 5.2% of the examined participants. Higher anxiety severity was associated with female sex, lower education level, German as a foreign language and younger age as well as high perceived stress and depression. Clinically relevant GAD symptoms as well as panic attacks are frequent in the NAKO and are associated with sociodemographic factors, and high anxiety symptoms are accompanied by pronounced stress and depression levels.
Online veröffentlicht: 17.Februar 2022
Gesehen am 11.06.2024